Cybersecurity knowledge and skills for port facility security officers of international seaports: Perspectives of IT and security personnel - Chalermpong Senarak (Elsevier, 2021)
Cyberattacks on worldwide port facilities have highlighted the urgent need for port facility security officers (PFSOs) to upgrade their cybersecurity knowledge and skills. This study used the survey data from all international container ports in Thailand and analyzed the results from two perspectives, i.e., IT and security officers. Based on 73 responses, cybersecurity knowledge and skill would become essential for PFSOs than ever before because the port digitalization and automation would shape the PFSOs career to a technically-oriented specialist rather than a multi-skilled generalist. Furthermore, the responsibilities of PFSOs would extend to cover cyber risk management, which enables them to prevent the digital port facilities from emerging cyber threats. Therefore, they should learn how to incorporate the existing risk management process with cyber risk management and cybersecurity knowledge because these would be the foundation for PFSOs to practice cybersecurity skills. At the end of the learning process, PFSOs could also gain cybersecurity competence once they have mature knowledge and skill, which would be the vital element of port security hygiene.